Finland and Sweden today, Southeast Asia tomorrow? - Yew Meng Lai; Cheng-Chwee Kuik (ThinkChina, 2021)
In light of Finland and Sweden's bids to join the North Atlantic Treaty Organization (NATO) in the wake of Russia's invasion of Ukraine, some observers have opined that small and secondary states in Southeast Asia will, sooner or later, join an alliance with "like-minded" powers. The underlying assumption is that autocratic China will act like autocratic Russia, and weaker states in Asia must act now to ensure their own security and preserve regional stability before it is too late.